2018
DOI: 10.1007/s41939-018-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization of WEDM parameters on machining 16MnCr5 alloy steel using Taguchi technique

Abstract: In this present work, an attempt has been made to optimize the wire electric discharge machining using muli-response optimization technique based on Taguchi's design approach. 16MnCr5 Alloy steel was selected as workpiece material. The response parameters viz. material removal rate and surface roughness were optimized by varying types of electrode, pulse on time (T on ), pulse off time (T off ) and peak current (I p ). The Taguchi's L 18 mixed orthogonal array has been used for planning and designing the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…According to Adik et al [15] machining of shape memory alloy with wire EDM yielded good surface finish compared to traditional machining process when machining at high T ON the surface finnish was observed to be rough with crack, craters and blow holes. According to Tushar et al [16] T ON is identified as the significant factor showing effect on material removal rate and surface finish. Higher the T ON , more is the surface roughness and material removal rate.…”
Section: Introductionmentioning
confidence: 99%
“…According to Adik et al [15] machining of shape memory alloy with wire EDM yielded good surface finish compared to traditional machining process when machining at high T ON the surface finnish was observed to be rough with crack, craters and blow holes. According to Tushar et al [16] T ON is identified as the significant factor showing effect on material removal rate and surface finish. Higher the T ON , more is the surface roughness and material removal rate.…”
Section: Introductionmentioning
confidence: 99%
“…When input current was varied from 10A to 20A, SR gets reduced, proving that higher current produces lower SR values. The rate of material removal upsurges with higher pulse on-time [33]. For MRR, the most significant parameter is pulse on-time [34].…”
Section: Resultsmentioning
confidence: 99%
“…Saini et al [14] achieved multi-objective optimization in WEDM of 16MnCr5 alloy steel. Obwald et al [15] conducted an analysis of different pulses types generated in high-speed WEDM.…”
Section: Introductionmentioning
confidence: 99%